(untitled) (Proceedings of Voronezh State University. Series: Geology, 2022)
Introduction: The Nerkayu eclogite-shale complex is located in the northern part of the Nether-Polar Urals and is represented by metamorphised rocks of various compositions. In earlier geophysical studies, it was noted that against the background of negative geophysical fields above the complex, its north-eastern part is characterised by a local increase in magnetic and gravitational fields [1, 2]. To understand the reasons for the increase in the intensity of local anomalies (ΔT)a and Δg, it is important to conduct of detailed petrophysical studies of metabasites. Petrographic and petrochemical data were also used to substantiate the degree of influence of metamorphic and metasomatic processes on the magnetic and density properties of the rocks. Methodology: The study of the physical properties (density and magnetic susceptibility) of metabasites was carried out with the help of instruments in the laboratory conditions. The magnetic susceptibility of the rocks in the form of powders was measured by the KAPPABRIGE KLY-2 system. Density was determined by hydroscopic weighing of solid rock samples using Mettler Toledo laboratory scales. The measured data were processed by the method of mathematical statistics [3]. Petrographic descriptions of rocks were given for polarised thin sections using a Polam-215 polarised-light microscope. Ore minerals were studied using a Tescan VEGA3 LMH scanning electron microscope. Results and discussion: Measurements of physical properties (mainly magnetic susceptibility and density) of metabasites of the Nerkayu complex allowed identifying certain patterns between the mineral composition of rocks, the degree of their metamorphic and metasomatic transformations, and their petrophysical properties. For example, despite a certain similarity in the petrophysical characteristics of amphibolites and eclogite-like rocks, the most fractional differentiation of metabasites was revealed in their magnetic properties. The comparison of magnetic properties of metabasites showed that diaphthorised and metasomatically altered (quartz bearing, albitised, chloritised, and carbonatised) amphibolites are the most magnetic. There is also a dependence of magnetic susceptibility of amphibolites on the content of ilmenite, magnetite, and titanomagnetite in them. Highly magnetic amphibolites are markers of the development of sites of noble metal mineralisation. Changes in the magnetic properties of eclogite-like rocks, in particular their increase, are also associated with secondary changes, namely with epidotisation. Conclusions: The results of a comprehensive study of the metabasites of the Nerkayu complex showed a distinct similarity in the nature of the distribution of physical properties of the rocks and a difference in the reasons for their variability. Statistical analysis of petrophysical characteristics in combination with the petrographic description revealed a fairly fractional differentiation of metabasites by their magnetic characteristics. A pronounced increased magnetisation and density resulted in positive anomalies of the magnetic field and gravitational fields [2] over the areas of metabasites’ exposure on the surface. In turn, a comprehensive interpretation of (ΔT)a and Δgl allowed dividing the Nerkayu complex into two parts: north-east (with positive anomalies) and south-west (with negative anomalies).